2013
DOI: 10.1002/hep.26070
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary syndrome: Favorable outcomes in the MELD exception era

Abstract: Hepatopulmonary syndrome (HPS) is a pulmonary vascular disorder occurring as a consequence of advanced liver disease, characterized by hypoxemia due to intrapulmonary vascular dilatations. HPS independently increases mortality, regardless of the cause or severity of liver disease. Liver transplantation (LT) improves survival in HPS. We present the largest consecutive series of HPS patients specifically addressing long-term survival relative to the degree of hypoxemia and the era in which LT was conducted. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
3
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 21 publications
3
91
3
7
Order By: Relevance
“…Some studies have suggested that very severe arterial hypoxaemia in HPS confers a worse prognosis with or without liver transplant [129,131,132], an observation that has not been replicated in all series [133].…”
Section: Current Status Of Pophmentioning
confidence: 99%
“…Some studies have suggested that very severe arterial hypoxaemia in HPS confers a worse prognosis with or without liver transplant [129,131,132], an observation that has not been replicated in all series [133].…”
Section: Current Status Of Pophmentioning
confidence: 99%
“…Pharmacological agents have not proven to be uniformly beneficial in HPS, and liver transplantation (LT) is currently the only effective treatment option available for these patients. [3][4][5] POPH, on the other hand, involves elevated pulmonary artery (PA) pressures (mean, MPAP) and increased PVR, as measured by right heart catheterization (RHC), because of generalized pulmonary arterial vasoconstriction and proliferative vasculopathy, with microthrombi, vascular remodeling, and plexiform changes. Symptoms include dyspnea, along with signs of right heart failure.…”
mentioning
confidence: 99%
“…Among other studies there´s the TAC and the single chest chamber, however it´s specificity and sensibility are low, for this reason its utilization would be indicated more to discard any respiratory etiology that may be causing hypoxemia [7][8][9][10][11]. Within the treatment, in some bibliographies, supplementary oxygen and hepatic transplant are mentioned as the only satisfactory answer.…”
Section: Pulmonary Angiography and Scintigraphymentioning
confidence: 99%